Proteomics analysis of rice seedling responses to ovine saliva - Fan, Weihong; Cui, Weitong; Li, Xiaofeng; Chen, Shuangyan; Liu, Gongshe; Shen, Shihua (Journal of plant physiology, 2011)
Grazing is accompanied by a multitude of processes including wounding, saliva deposition, and defoliation. Previous studies have focused on the effects of the grazing or clipping intensity on plant regrowth, survival, and composition in the grassland. However, the impact of saliva deposition on plants is poorly understood. In this study, rice was used as a model plant to study the differentially expressed proteins after ovine saliva treatment. The shoots of 2-week-old seedlings were crosscut and the lower parts were daubed with ovine saliva at the cut surface. After 2, 6, 12 and 24 h, proteomics analysis was performed using proteins extracted from the saliva-treated shoots. The results showed that proteins involved in multiple pathways were differentially expressed in response to ovine saliva, including catalase (CAT), peroxiredoxin (Prx), ATP synthase, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). Moreover, real-time quantitative reverse-transcription-PCR (RT-PCR) data showed that most of the genes were also regulated at the transcript level. Our results indicate the ovine saliva induces an early response in the rice seedling by stress-related pathways. This study provides information about the response of rice seedlings to ovine saliva at the protein level.